Measuring Mutual Fund Performance with Characteristic-Based Benchmarks - Daniel, Kent; Grinblatt, Mark; Titman, Sheridan; Wermers, Russ (Journal of Finance, 1997)
Kent Daniel, Mark Grinblatt, Sheridan Titman, Russ Wermers, Measuring Mutual Fund Performance with Characteristic-Based Benchmarks, The Journal of Finance, Vol. 52, No. 3, Papers and Proceedings Fifty-Seventh Annual Meeting, American Finance Association, New Orleans, Louisiana January 4-6, 1997 (Jul., 1997), pp. 1035-1058